LO QUE NOS DICE LA HISTORIA DE LA ENSEÑANZA DE LA BIOLOGÍA EN COLOMBIA —UNA APROXIMACIÓN— - Varios, Autores (Tecné, Episteme y Didaxis: TED, 1998)
We have few information about the history of teaching Biology in Colombia. From the historic and social analysis, it is possible to recognize the influence of the elements of power and knowledge that come from normative institutions about practice in the teaching of Biology in Colombia. The article describes four historical moments and what we have called mixed knowledge, circumscribed knowledge, biological science and professionalization.